COMPARISION OF CHILDREN'S MOTOR COORDINATION IN DIFFERENTS AGES (Fiep Bulletin - online, 2011)
The aim of the present study was to compare the motor coordination of children in different ages. The subjects were 56 children of both genders, aged between 9 and 12 years (mean=10,5 + 1,1), being utilized the KTK test (Körperkoordination Test für Kinder) to analyze motor coordination of the subjects. The test was consisted of four tasks. The balance beam which evaluates the walking back balance stability; the one foot jump which verifies the inferior member coordination, dynamic power/ strength; the lateral jump evaluates the speed in alternate jumps and transfer on platform which analyze laterality and space-time structural. The measurements were presented through performance that was attributed a score in the form of the sum of the four tasks. In performance analysis, the nine years old children´s group had the best results followed to ten, eleven and twelve years old. However, statistical analysis using Kruskal- Wallis test didn't detect difference among the groups. The present results can be related with the subjects' previous experiences or a difficulty of the test to detect difference among the groups.
Keywords: Coordination; Children; Motor skills